Targeting KNDy neurons to control GnRH pulses. (December 2022) - Constantin, Stephanie
Abstract: Gonadotropin-releasing hormone (GnRH) is the final output of the central nervous system that drives fertility. A characteristic of GnRH secretion is its pulsatility, which is driven by a pulse generator. Each GnRH pulse triggers a luteinizing hormone (LH) pulse. However, the puzzle has been to reconcile the synchronicity of GnRH neurons with the scattered hypothalamic distribution of their cell bodies. A leap toward understanding GnRH pulses was the discovery of kisspeptin neurons near the distal processes of GnRH neurons, which secrete kisspeptins, potent excitatory neuropeptides on GnRH neurons, and equipped with dual, but opposite, self-modulatory neuropeptides, neurokinin B and dynorphin. Over the last decade, this cell-to-cell communication has been dissected in animal models. Today the 50-year quest for the basic mechanism of GnRH pulse generation may be over, but questions about its physiological tuning remain. Here is an overview of recent basic research that frames translational research.